ANALYSIS OF FOREST COVER CHANGES IN RIVER BASINS FLOWING INTO LAKE SEVAN (Proceedings of the YSU C: Geological and Geographical Sciences, 2023)
The paper presents spatial and temporal changes and the current situation of forests in the Lake Sevan basin. The general physico-geographic characteristics of the Sevan basin, the detailed characteristics of the forests in the Sevan lake basin, the natural and anthropogenic changes are presented, and an analysis of the cause and effect relationships of these changes is carried out. The changes in the forest cover and the negative aquatic biological processes that appeared in the lake’s ecosystem as a result of the program of cutting down the water-covered and subject to water-covering forests in the Sevan Lake basin, implemented since 2005, were analyzed. The necessity of increasing forest cover, preventing negative aquatic biological processes in the lake ecosystem and restoring ecological balance through the creation of new forest belts in the lake basin is substantiated. A number of practical proposals are presented to restore the ecological balance of the lake, to prevent negative aquatic biological processes in the lake's ecosystem: afforestation of sloping slopes and erosion-prone areas, strengthening of coastal protection measures, etc. Research is needed to determine the optimal level of the lake in the future, taking into account the changing ecological conditions in the lake basin.
Keywords: forest cover; afforestation; ecological balance